2018
DOI: 10.1007/s11883-018-0738-6
|View full text |Cite
|
Sign up to set email alerts
|

Mindset and Communication Barriers in the Diffusion of Bariatric Surgery

Abstract: general practitioners who already referred patients for BS seem to be more confident to refer again, to tackle obesity and manage postoperative follow-up. Confirmation: postbariatric patients seem to be more self-confident and more productive at work; however, their stigmatization might prevail related to the way they have achieved weight loss. Dissemination of balanced and corroborative information seems to be the main instrument to combat mindset barriers. The integration of general practitioners under the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Based on a literature review on mindset and communication barriers towards BS, barriers mainly arise from absent or incorrect information about obesity as chronic disease and its therapy option. 17 Consequences may be inadequate treatment of obesity, underestimation of the risk of severe obesity—and delayed decision‐making on the next therapy escalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a literature review on mindset and communication barriers towards BS, barriers mainly arise from absent or incorrect information about obesity as chronic disease and its therapy option. 17 Consequences may be inadequate treatment of obesity, underestimation of the risk of severe obesity—and delayed decision‐making on the next therapy escalation.…”
Section: Discussionmentioning
confidence: 99%
“…The belief of being self‐responsible for the obesity is instilled in those patients over years—also by healthcare professionals. 17 , 19 , 20 A recent study from Saudi Arabia revealed that most patients blame low self‐discipline as one of the main reasons for poor adherence to diet and exercise after BS. 21 Hence, every so‐called therapy failure may stoke the feeling of shame, weakness and guilt and maintains the negative spiral of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Bezogen auf die Einwohnerzahl war das Missverhältnis zwischen effektiven Patientenzahlen und tatsächlich durchgeführten bariatrischen Eingriffen in Deutschland jahrelang besonders auffällig [ 2 , 4 ]. Unzweifelhaft ist die weit verbreitete Stigmatisierung der Erkrankung „Adipositas“ sowohl bei Betroffenen als auch bei therapeutischen Spezialisten eine wesentliche Ursache für diese Situation [ 5 , 9 , 10 ]. Große Bedeutung für die fehlende flächendeckende Verbreitung der Adipositaschirurgie hat aber ebenso die restriktive Politik hinsichtlich der Übernahme der Behandlungskosten durch die Kostenträger.…”
Section: Diskussionunclassified
“…Stigmatization and discrimination of patients with overweight or obesity increased over the last decades in Western countries [1][2][3]. Weight bias toward patients with obesity is also common among healthcare professionals, including primary care physicians [4,5], and has even been reported in medical students [6][7][8].…”
Section: Introductionmentioning
confidence: 99%